The Dynamic Game of Knowledge Hiding Behavior from Organizational Members: To Hide or Not to Hide? - Fan Yang; Long Yang; Ping Li (Complexity)
In the era of the knowledge economy, it is urgent for organizations to solve the problem of knowledge hiding of internal members to accelerate the speed and efficiency of knowledge dissemination and innovation and adapt to rapid changes in the market. At present, research on knowledge hiding has received extensive attention from Western countries, but there are few relevant studies in China. Based on the hypothesis of bounded rationality, this paper constructs an evolutionary game model of second-level knowledge hiding of organizational members and analyzes the main factors affecting the stable equilibrium point using MATLAB numerical simulation. The results show that knowledge leakage risk is positively correlated with knowledge hiding. The ability of knowledge absorption and transformation is positively correlated with the behavior of knowledge hiding. There is a negative correlation between collaborative innovation ability and knowledge hiding. There is a negative correlation between knowledge stock and knowledge hiding. Only when the incentive reaches a certain level can organizational members be encouraged to give up knowledge hiding. This paper provides a more comprehensive and dynamic picture of the evolutionary game of knowledge hiding among members in the organization and provides a new idea of knowledge management for organizational managers.